Estrogen May Enhance Toll-Like Receptor 4-Induced Inflammatory Pathways in People With HIV: Implications for Transgender Women on Hormone Therapy - Kettelhut, Aaren; Bowman, Emily; Gabriel, Janelle; Hand, Brittany; Liyanage, Namal P. M.; Kulkarni, Manjusha; Avila-Soto, Frances; Lake, Jordan E.; Funderburg, Nicholas T. (Frontiers in Immunology, 2022)
Background: Transgender women (TW) are at increased risk for both human immunodeficiency virus (HIV) and cardiovascular disease (CVD). Antiretroviral therapy-treated HIV has been associated with a two-fold increased risk of CVD, potentially due to dysregulated Toll-like receptor (TLR)-induced immune activation. Use of estrogens in feminizing hormone therapy (FHT) may enhance inflammatory responses and the risk of cardiovascular mortality in TW. Despite this, the immunomodulatory effects of estrogen use in TW with HIV have been inadequately explored. Methods: As an in vitro model for FHT, cryopreserved PBMCs (cryoPBMCs) from HIV negative (HIV-), HIV+ ART-suppressed (HIV+SP), and HIV+ ART-unsuppressed (HIV+USP) cisgender men were cultured overnight in the presence of 17-β estradiol or 17-α ethinylestradiol with and without the TLR4 agonist LPS or the TLR8 agonist ssPolyU. Monocyte activation (CD69, HLA-DR, CD38) was assessed by flow cytometry. Cytokine levels (IL-6, TNF-α, IL-1β, and IL-10) were measured in cell culture supernatants by Legendplex. Levels of phosphorylated TLR signaling molecules (JNK, MAPK p38) were assess by Phosflow. Plasma levels of immune activation biomarkers (LPS-binding protein, monocyte activation markers sCD14 and sCD163, and inflammatory molecules IL-6 and TNF-α receptor I) were measured by ELISA. Results: PBMCs from people with HIV produced increased levels of inflammatory cytokines following exposure to LPS or ssPolyU compared to levels from cells of HIV- individuals. While estrogen exposure alone induced mild changes in immune activation, LPS-induced TLR4 activation was increased with estrogen in CM with HIV, increasing monocyte activation and inflammatory cytokine production (IL-6, TNF-α). Interestingly, testosterone inhibited LPS-induced cytokine production in cisgender men (CM) regardless of HIV status. Plasma markers of immune activation and microbial translocation (e.g., sCD14, sCD163, LPS-binding protein) were generally higher in PWH compared to HIV- CM, and these markers were positively associated with in vitro responsiveness to estrogen and LPS in CM with HIV. Conclusions: Our in vitro data suggest that estrogen exposure may enhance innate immune activation in people with HIV. Further examination is needed to fully understand the complex interactions of FHT, HIV, and CVD in TW, and determine optimal FHT regimens or supplementary treatments aimed at reducing excess immune activation.